Preliminary Remarks on De Facto Government and the Problem of Its Legitimacy: Imam Al-Juwayni’s Theory of AL-Shawkah - Jah, Omar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Preliminary Remarks on De Facto Government and the Problem of Its Legitimacy: Imam Al-Juwayni’s Theory of AL-Shawkah